Monocarboxylate transporter 4 as a prognostic biomarker in patients with colorectal cancer and liver metastases. (2016) - Petrides, Christos; Neofytou, Kyriakos; Agrogiannis, Georgios; Petrou, Athanasios; Angelou, Anastasios; Kavantzas, Nikolaos; Papalambros, Alexandros; Felekouras, Evangelos; Liakakos, Theodoros; Pikoulis, Emmanouel
Highlights: We validated the prognostic significance of the expression of MCT4 in colorectal liver metastases. Strong stromal MCT4 expression was associated with decreased DFS and OS. MCT4 could be used as a new biomarker. MCT4 could be used in target therapy. Abstract: Objective: This study aims to validate the prognostic significance of the expression of Monocarboxylate Transporter 4 (MCT4) in patients with colorectal liver metastases (CRLM). This study investigated the correlation between MCT4 expression in stromal and tumor cells of colorectal liver metastases (CRLM) with disease-free (DFS) and overall survival (OS) in liver-only colorectal metastases treated with liver resection following neoadjuvant chemotherapy. Methods: This is a retrospective study of 107 patients with colorectal liver metastases. MCT4 expression in both stromal and tumor cells was studied by immunohistochemistry. The staining was scored semiquantitatively as weak or strong. DFS and OS were calculated using both Kaplan–Meier and multivariate Cox-regression methods Results: Specimens from 57 patients (53.27%) showed weak levels of stromal MCT4 staining, whereas 50 patients (46.73%) showed strong levels of MCT4 staining. From the statistical analysis, strong stromal MCT4 expression was associated with decreased DFS (HR 1.79; 95% CI, 1.12–2.85; P = 0.014) and OS (HR 3.81 95% CI, 1.88–7.72; P < 0.001) in univariate analysis. This finding remained significant in multivariate analysis for both DFS and OS (HR 1.95; 95% CI, 1.19–3.17; P = 0.007, and HR 4.38; 95% CI, 2.15–8.92; P < 0.001 respectively). Tumeur MCT4 expression was not associated with DFS and OS. Five-years DFS and OS rates were 43% and 78% respectively in patients with weak and 15% and 37% respectively in patients with strong stromal MCT4 expression. Conclusion: Our results indicated that strong expression of stromal MCT4 in CRLM was associated with poor prognosis in patients who undergo liver resection for liver-only colorectal metastases. This finding could be furthermore validated in independent studies and MCT4 could be used as a new biomarker in CRLM and creates the possibility of new studies in targeted therapies.